Co-Chairs’ Summary Report from the Second Meeting of the TFTIA - TFTIA Co-Chairs (Arctic Council Secretariat, 2016)
"Norway hosted the second meeting of the Arctic Council’s Task Force on Telecommunications Infrastructure in the Arctic (TFTIA-02) in Tromsø on 8-9 February, 2016. The TFTIA’s mandate is to “coordinate a circumpolar assessment of telecommunications infrastructure and networks. The Task Force would deliver a completed assessment to include, among other things, recommendations for public-private partnerships to enhance telecommunications access and service in the Arctic.” The TFTIA is co-chaired by Norway (represented by Bo Andersen) and the Kingdom of Denmark (represented by Niels Andersen)."